Seeing Red: Color Selection as an Indicator of Implicit Societal Conceptions about the Autism Spectrum - Joshua John Diehl; Julie Wolf; Lauren Herlihy; Arlen C. Moller (Disability Studies Quarterly, 2011)
We explore how implicit associations with the label "autism" influence how people with the diagnosis are represented and perceived. A recent trend in public discourse has been to add descriptors to autism, such as "high-functioning" or "spectrum," possibly to minimize the perceived stigma associated with the diagnosis. We examined the colors used by researchers in poster graphs to represent the term autism. Research has indicated that the color red has implicit negative associations when evaluation of competence is salient. We found that red was used more often for groups with an autism label than other groups. Further, the use of red was less frequent when there were qualifiers for autism such as "high-functioning," "spectrum," or for Asperger syndrome. We assert that this pattern is evidence of implicit, negative societal associations with the word autism that influence discourse on the diagnosis.
Keywords: Autism; Asperger syndrome; stigma; red; color; implicit attitudes; visual rhetoric